Communicative Competence Approach to Person-Oriented Teaching of the Russian Language and Culture of Speech - Y. V. Orlova (Образование и наука)
The paper is devoted to the communicative competence approach in professional training of physicians on the undergraduate level. The main emphasis is on developing linguistic, sociolinguistic and pragmatic competences while teaching the Russian language and the culture of speech. The paper is aimed at analyzing the requirements of federal state educational standards of the 3rd generation concerning the competences in the humanities which should be developed by medical students in the course of the Russian language and the culture of speech; defining the contents of the «communicative competence» term based on consideration of general European competences in mastering the language and the analysis of lingua-didactic works of modern Russian scientists; identifying the component content of linguistic, sociolinguistic and pragmatic competences of the Russian language and the culture of speech course for medical schools. The research results regarding the analysis and component content of linguistic, sociolinguistic and pragmatic competences of the Russian language and the culture of speech course have been applied while designing the Russian and the culture of speech curriculum, as well as electronic textbooks and manuals for medical students.